Challenges to Family Management for Caregivers of Adolescent and Young Adult Survivors of Childhood Brain Tumors. (November 2019) - SanGiacomo, Nicole; Toth, Jennifer; Hobbie, Wendy; Broden, Elizabeth; Ver Hoeve, Elizabeth; Knafl, Kathleen A.; Barakat, Lamia; Ogle, Sue; Deatrick, Janet A.
Due to the complexity of cancer late effects, the education required to provide anticipatory guidance and support to the caregivers of adolescent and young adult (AYA) survivors of childhood brain tumors can be difficult. Therefore, identifying challenges to family management (FM) could be helpful in anticipating complications with the integration of tumor and treatment late effects into family life. Building on previous research that described FM for children with chronic conditions, children who survived cancer, and the Family Management Styles Framework, the purpose of this study was to identify FM challenges for caregivers of AYA survivors of childhood brain tumors to guide clinical practice and research. Directed content analysis was used to identify FM challenges in data from semistructured interviews with 45 maternal caregivers for AYA survivors of childhood brain tumors living with them. Caregivers were largely White (89%) with an average age of 52 years, educated beyond the high school level (67%), and were partnered or married (53%). On average, caregivers had been caring for the AYA for 21 years since diagnosis, and 56% of their survivors had moderate functional restrictions. A primary and a secondary analyst were assigned to the data for each interview and completed a single summary matrix. A list of challenges was created by the research team based on Family Management Styles Framework, the literature, and clinical expertise. Seven core challenges to FM were identified: ensuring survivor well-being, supporting survivor independence, encouraging sibling well-being, planning family activities, sustaining parents as caregivers, attending to survivor late effects, and providing support and advocacy.